Vitamin D Status and Immune Response in Hospitalized Patients with Moderate and Severe COVID-19 - Tatiana L. Karonova; Igor V. Kudryavtsev; Ksenia A. Golovatyuk; Arthur D. Aquino; Olga V. Kalinina; Alena T. Chernikova; Ekaterina K. Zaikova; Denis A. Lebedev; Ekaterina S. Bykova; Alexey S. Golovkin; Evgeny V. Shlyakhto (MDPI AG, 2022)
A low 25-hydroxyvitamin D (25(OH)D) level is considered as an independent risk factor for COVID-19 severity. However, the association between vitamin D status and outcomes in COVID-19 is controversial. In the present study we investigate the association between the serum 25(OH)D level, immune response, and clinical disease course in patients with COVID-19. A total of 311 patients hospitalized with COVID-19 were enrolled. For patients with a vitamin D deficiency/insufficiency, the prevalence of severe COVID-19 was higher than in those with a normal 25(OH)D level (p < 0.001). The threshold of 25(OH)D level associated with mortality was 11.4 ng/mL (p = 0.003, ROC analysis). The frequency of CD3+CD4+ T helper (Th) cells was decreased in patients with 25(OH)D level ≤ 11.4 ng/mL, compared to healthy controls (HCs). There were no differences in the frequency of naive, central memory (CM), effector memory (EM), and terminally differentiated effector memory Th cells in patients with COVID-19 compared to HCs. The frequency of T-follicular helpers was decreased both in patients with 25(OH)D level > 11.4 ng/mL (p < 0.001) and 25(OH)D level ≤ 11.4 ng/mL (p = 0.003) compared to HCs. Patients with 25(OH)D level > 11.4 ng/mL had an increased frequency of Th2 CM (p = 0.010) and decreased Th17 CM (p < 0.001). While the frequency of Th2 EM was significantly increased, the frequency of Th17 EM was significantly decreased in both groups compared to HCs. Thus, 25(OH)D level is an independent risk factor for the disease severity and mortality in patients with COVID-19. We demonstrate that the serum 25(OH)D level ≤ 11.4 ng/mL is associated with the stimulation of Th2 and the downregulation of Th17 cell polarization of the adaptive immunity in patients with COVID-19.